2015
DOI: 10.1097/npt.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Assessment Across the Disability Spectrum in Persons With Multiple Sclerosis

Abstract: Overall, peak physical capacity was higher when assessed by recumbent stepping and computerized dynamometry. The assessment and prescription of exercise in MS should be based on these modalities to provide the most appropriate stimulus for exercise training adaptations. There continues to be an important association between physical fitness and other measures that represent all domains of the ICF, regardless of fitness assessment mode.Video Abstract available for additional insights from the authors (see Video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 36 publications
1
58
1
Order By: Relevance
“…These results extend previous findings of Pilutti et al, 22 who found that HHD was able to discriminate among mild, moderate, and severe disability in the knee extensors and flexors. Together, these findings support the ability of strength measurepreviously published values for people with MS in the trunk flexion test (29.48 ± 17.76 repetitions) 38 and for controls in the ankle plantarflexion endurance (range, 28.0-29.8 repetitions) 36 and trunk extension (range, 141-197 seconds) 43 tests.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These results extend previous findings of Pilutti et al, 22 who found that HHD was able to discriminate among mild, moderate, and severe disability in the knee extensors and flexors. Together, these findings support the ability of strength measurepreviously published values for people with MS in the trunk flexion test (29.48 ± 17.76 repetitions) 38 and for controls in the ankle plantarflexion endurance (range, 28.0-29.8 repetitions) 36 and trunk extension (range, 141-197 seconds) 43 tests.…”
Section: Resultssupporting
confidence: 82%
“…Little has been reported on discriminant validity of strength measured by HHD in people with neurologic conditions. 21 In people with MS, HHD measurements of knee strength have been shown to discriminate between disability levels, 22 but, to our knowledge, discriminant validity of HHD between people with MS and controls has not been reported.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Participants were fitted to the stepper and received instructions on testing procedures along with instructions for reporting rating of perceived exertion (RPE). After being fitted with a mouthpiece (Hans Rudolph Inc, Kansas City, MO) for collecting expired gases, participants performed a 1-minute warm-up at 15 W. The initial work rate for the exercise test was 15 W, and the work rate continuously increased at a rate of 5 W/min until the participant reached volitional fatigue.…”
Section: Cardiorespiratory Capacitymentioning
confidence: 99%
“…This cross-sectional study involved a secondary data analysis from a previous research study aiming to develop fitness testing protocols for people with MS. 17,18 Briefly, prospective participants were contacted through the North American Research Committee on Multiple…”
Section: Participantsmentioning
confidence: 99%